Memoirs of an Unsung Legend, Nemeso - Mawere, Munyaradzi; Mabeza, Christopher; Mukombe, Cosmas M. (Book collections on Project MUSE., 2013)
Nemeso - a four eyed man-lived in southeastern Zimbabwe in the mid-17th century. Stories about him are widely known by the Duma in southeastern Zimbabwe as he left a legacy, a delicious dish - of edible stinkbugs locally named harurwa. These insects, believed to be a gift to Nemeso by the ancestors, thrive in a grove (jiri) where no one has been allowed to meddle since the time of Nemeso, the medium through whom the stinkbugs were gifted to the living by the living-dead. The insects are a source of livelihood for the Duma people and for people beyond, and serve as a drive for forest conservation in the area. The wealthy stories of Nemeso's life have been passed on through oral tradition. This book, generated from an ethnographic reconstitution in southeastern Zimbabwe, documents the stories in a lively and fascinating thirst quenching manner.